Exploring the relationship between newspaper coverage of vaccines and childhood vaccination rates in Spain - Daniel Catalan-Matamoros; Carmen Peñafiel-Saiz (Human Vaccines & Immunotherapeutics, 2020)
Background: Despite the effectiveness of vaccines being well established and recognized by the research community, eleven European countries have adopted mandatory vaccination programs because of vaccine hesitancy. Lack of information and fake news are considered the main reasons. The media are a powerful tool for spreading vaccine-related information. The study of media effects on vaccine uptake has received little attention in Europe. Objective: To explore the association of childhood vaccination rates in Spain with vaccine-related coverage in print media. Methods: A content analysis of newspaper coverage of vaccines was conducted. The study variables were: national vaccination rates, article publication dates, tone and main theme of the articles. We conducted a correlation analysis to assess the association between media coverage and childhood vaccine uptake. Results: While vaccine coverage with positive and neutral tones significantly increased during the study period (p < .001), the number of articles with a negative tone remained unchanged (p = .306). There was a significant and inverse correlation between negative newspaper coverage and childhood vaccine uptake (r = −.771, p < .05). During 2016 and 2017, although the media reporting declined, vaccination rates kept increasing. The most frequent themes were about the development of the Ebola vaccine, and the chickenpox and meningitis vaccine crises. Conclusions: Our findings expand the understanding of media role on vaccination and suggest that the media need to be considered as an important player during vaccination campaigns. The study points to the important educational role of the media in public health.